ANALISIS KOMBINASI WARNA PADA ANTARMUKA WEBSITE PEMERINTAH KABUPATEN KLATEN - Sasongko, Muhammad Nurcahyo; Suyanto, M; Kurniawan, Mei P (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2020)
The combination of colors of a website is one of the most important things to make an attractive website look. To determine the color combination of a website, it is necessary to pay attention to the proper harmonization and contrast. This research is conducted on the website of the Klaten Regency Government. The purpose of this research is to determine the color combination based on the desires of the website visitors. The method used is the theory of color psychology by Goethe and Itten, using the Color Extraction tool to find the dominant colors. The preparation of the questionnaire is assisted by psychologists, and the results of the questionnaire are used as references to determine the new color combinations of the website. 77 website visitors like the new color combinations created based on psychological questionnaires, therefore, it can be concluded that the new color combinations are accepted by the website visitors. This research proves that color determination based on the color psychology can be implemented in the website color combinations’ construction.